ASEAN and European Human Rights Mechanisms, What Should be Improved? - Nurhidayatuloh Nurhidayatuloh; Febrian Febrian (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2019)
AbstractThe human rights mentioned in the Universal Declaration on Human Rights (UDHR) are universal values agreed upon countries in the world. This is reflected by the fact that no state rejects the United Nations General Assembly Resolution in 1948. It is even strengthened by the ratification of two major international human rights covenants, which have binding legal powers. They are the International Covenant on Civil and Political Rights and the Covenant on Economic, Social, and Cultural Rights in 1966. European states are legally bound to human rights through the European Human Rights Convention that is signed in 1950 and come into force in 1953. On the other hand, ASEAN states are bound to human rights as parties of ICCPR, ICESCR, and their commitment to the regional level ASEAN Declaration of Human Rights. Both in European Union and ASEAN have their own human rights mechanisms: the European Court of Human Rights (ECtHR) and ASEAN Intergovernmental Commission on Human Rights (AICHR). This study employed a comparison method with a normative legal research approach to compare the human rights mechanisms in Europe and in ASEAN. It also deals with the implementation of human rights protection by the states in the two regional organizations. As a result, although the two regional organizations have human rights mechanisms applied in their areas, with experiences through cases appealing to European Human Rights Courts, Europe provides more assurance and legal certainty towards individuals when a state commit human rights violations against individuals. On the other hand, the AICHR, as the equal commission in ASEAN region, tends not to have sufficient legal power in handling human rights cases occurred in its territory.Mekanisme HAM ASEAN dan Eropa, Apa yang Seharusnya Dibenahi? AbstrakHak asasi manusia yang terdapat dalam DUHAM merupakan nilai-nilai universal yang telah disepakati oleh negara-negara di dunia. Hal ini tercermin dengan tidak adanya satupun negara yang menolak Resolusi Majelis Umum PBB tersebut tahun 1948 dan diperkuat dengan disahkannya dua kovenan internasional utama HAM yang mengikat yakni Kovenan tentang Hak Sipil dan Politik (ICCPR) dan Kovenan tentang Hak Ekonomi, Sosial dan Budaya (ICESCR) tahun 1966. Negara-negara di Eropa memiliki keterikatan secara hukum terhadap HAM melalui Konvensi HAM Eropa yang disahkan tahun 1950 dan berlaku 1953. Di sisi lain, negara-negara di ASEAN memiliki keterikatan terhadap HAM sebagai pihak ICCPR, ICESCR dan komitmen mereka terhadap Deklarasi HAM ASEAN pada tingkat regional. Baik di organisasi regional Eropa maupun ASEAN memiliki mekanisme HAM masing-masing, Eropa memiliki Pengadilan HAM Eropa dan ASEAN memiliki Komisi HAM ASEAN. Artikel ini menggunakan metode perbandingan dengan pendekatan penelitian hukum normatif yakni dengan membandingkan mekanisme HAM yang ada di Eropa dan di ASEAN dan implikasinya terhadap praktik perlindungan HAM oleh negara di dua organisasi regional tersebut. Hasil penelitian ini adalah meskipun kedua organisasi regional tersebut sama-sama memiliki mekanisme HAM yang berlaku di wilayah mereka, dengan pengalaman yang dimiliki Eropa melalui Pengadilan HAM, Eropa lebih memberikan jaminan dan kepastian hukum terhadap individu ketika negara melakukan pelanggaran HAM terhadap individu. Di sisi lain, AICHR sebagai komisi yang berwenang untuk menyelesaikan persoalan HAM di wilayah ASEAN cenderung tidak memiliki kekuasaan dan kekuatan hukum yang memadai dalam menangani kasus-kasus HAM yang terjadi di wilayahnya.DOI: https://doi.org/10.22304/pjih.v6n1.a8